Isoniazid Could Be Used for Antibiotic-loaded Bone Cement for Musculoskeletal Tuberculosis: An In Vitro Study - Han, Chang Dong (Springer-Verlag, 2013)
BACKGROUND: Antibiotic-loaded bone cement (ALBC) has been used in serious cases of musculoskeletal tuberculosis, but the type and amount of antibiotic that should be used in ALBC have not been determined. QUESTIONS/PURPOSES: We therefore determined the (1) elution characteristics and (2) antimycobacterial activity of isoniazid- and rifampicin-loaded bone cement. METHODS: A total of 240 elution samples of each of three discs from 40 g bone cement mixed with one of eight dosages: 1 g, 2 g, and 4 g isoniazid, 1 g, 2 g, and 4 g rifampicin, and a combination of 1 + 1 g or 2 + 2 g of isoniazid and rifampicin. The polymerization of rifampicin-loaded bone cement was delayed to mean 122.5 ± 31.1 minutes. We measured the quantity of isoniazid and rifampicin and the antimycobacterial activity on Days 1, 3, 7, 14, and 30. RESULTS: Isoniazid eluted in almost all the samples while rifampicin was detected only on Day 1 with 2 g (0.7 ± 0.4 ug/mL/day), and until Day 14 with 4 g (0.1 ± 0.0u g/mL/day). Most of the samples containing isoniazid showed antimycobacterial activity while the samples containing rifampicin showed antimycobacterial activity only on Day 1 with 1 g (0.52 ± 0.18 ug/mL), until Day 14 with 2 g (0.03 ± 0.00 ug/mL), and until Day 30 with 4 g (1.84 ± 1.90 ug/mL). CONCLUSION: Rifampicin was unsuitable for ALBC because of its delayed polymerization. Isoniazid eluted and showed antimycobacterial activity for 30 days. CLINICAL RELEVANCE: The data suggest isoniazid could be considered for use in ALBC for musculoskeletal tuberculosis if used with systemic treatment. For preventing resistance and systemic toxicity, a combination with a second-line drug and an in vivo study would be needed.